5
$\begingroup$

In chapter 13 of the textbook of Group Theory in Physics by Wu-Ki Tung, Lemma 2 discusses the equivalence of two irreducible representations of GL(m) on ${T^i}_j$. In its proof, it simply mentioned (without deeper arguments as if it is quite obvious) that the contraction two tensors is zero if their indices belong to different symmetry types. I have thought it over for some time but really cannot figure out a proof of this statement.

Let me try to state the question more clearly below. Consider a tensor $T^a$ where $a$ refers to a list of contravariant indices, like $T^{1234}$. Now one may symmetrize this tensor according to a given Young Tableaux, namely $\tau$, and the resulting tensor is denoted by

$$T^{\tau(a)}.$$

It is noted that, according to theorems on representations of symmetric group $S_n$, $\tau$ corresponds to a irreducible representation of $S_n$. Now one considers a covariant tensor ${T'_b}$ and a different Young Tableaux $\lambda$, where $b$ contains the same number of indices, $\tau$ and $\lambda$ are not equivalent (one may assume $\tau$ > $\lambda$ without loss of generality). It is stated that the contraction

$$T^{\tau(a)}T'_{\lambda(a)}=0.$$

It is obviously true when $\tau$ corresponds to the symmetrizer and $\lambda$ is the anti-symmetrizer. But I cannot think of the proof for a general case.

$\endgroup$

migrated from physics.stackexchange.com May 17 '15 at 15:02

This question came from our site for active researchers, academics and students of physics.

  • $\begingroup$ What I was trying was to build a proof following similar arguments one might use for the simple case of symmetrizer and anti-symmetrizer, in this case exchange any two index in the contraction will do the job. I found out (according to Lemma IV.3 of the same book) when $\tau$ and $\lambda$ are inequivalent, there must be two numbers in the same row of Young Tableaux $\tau$ also appear in a same column of $\lambda$. And I thought that these two numbers can be considered as the two indices to be exchanged to obtain the proof except I could not. $\endgroup$ – gamebm May 15 '15 at 21:48
  • $\begingroup$ One need to multiply a transposition (of these two numbers) before $\tau$, while multiply the same transposition after $\lambda$ to get the extra -1 from $\lambda$. But exchanging two indices in the contraction, one need to multiply the transposition before both tensors. So I got nowhere... $\endgroup$ – gamebm May 15 '15 at 21:50
  • $\begingroup$ Following this argument, the best I can get is when at least one of the Young Tableaux (between $\tau$ and $\lambda$) is a symmetrizer or anti-symmetrizer, the contraction gives zero. $\endgroup$ – gamebm May 16 '15 at 19:00
3
$\begingroup$

If $\sigma$ is a permutation, then $T^{\sigma(a)}{T'}_{a}=T^{a}{T'}_{\sigma^{-1}(a)}$. If a permutation is part of a symmetrizer for a Young tableaux, then so is its inverse, so $T^{\tau(a)}{T'}_{a}=T^{a}{T'}_{\tau(a)}$. So $T^{\tau(a)}{T'}_{\lambda(a)}=T^{a}{T'}_{\tau(\lambda(a))}=0$.

$\endgroup$
  • $\begingroup$ Thanks a lot for the proof! If $\sigma$ and $\sigma^{-1}$ are both part of symmetrizer for a Young tableaux $\tau$, $\sigma\tau=\sigma^{-1}\tau=\tau$, then why $T^{\tau(a)}T'_a=T^aT'_{\tau(a)}$? Just by looking at the expression, all I can think is that symmetrizer does not have inverse in general(?), why can one exchange the summed indices in $T$ and $T'$? $\endgroup$ – gamebm May 16 '15 at 16:08
  • $\begingroup$ I got it. You mean $(T^{e(a)}+T^{\sigma_1(a)}+T^{\sigma_2(a)}+\cdots)T'_a=T^a(T'_{e(a)}+T'_{{\sigma_1}^{-1}(a)}+T'_{{\sigma_2}^{-1}(a)}+\cdots)$ and $e+\sigma_1+\sigma_2+\cdots=\lambda=e+\sigma_1^{-1}+\sigma_2^{-1}+\cdots$, where $\lambda \equiv e_\lambda$. $\endgroup$ – gamebm May 16 '15 at 18:22
  • $\begingroup$ Since for an idempotent corresponding to a general Young Tableaux, the inverse of a permutation is not necessarily a part of the sum. One may get the following $\lambda \equiv e_\lambda=s_\lambda a_\lambda=(e+\sigma_1+\sigma_2+\cdots)(1+(-1)^{\nu_{\omega_1}}\omega_1+(-1)^{\nu_{\omega_2}}\omega_2+\cdots)=(e+\sigma_1^{-1}+\sigma_2^{-1}+\cdots)(1+(-1)^{\nu_{\omega_1}}\omega_1^{-1}+(-1)^{\nu_{\omega_2}}\omega_2^{-1}+\cdots)$. $\endgroup$ – gamebm May 16 '15 at 20:08
  • $\begingroup$ But it seems that we do not have $T^{\sigma\omega(a)}T'_a=T^aT'_{\sigma^{-1}\omega^{-1}(a)}$ (?) $\endgroup$ – gamebm May 16 '15 at 20:09
0
$\begingroup$

I figured out the following proof. Considering the following primitive idempotent

$$\tilde{e}_\lambda \equiv a_\lambda s_\lambda,$$

one can show that it is equivalent to $e_\lambda$, since $\tilde{e}_\lambda e_\lambda = a_\lambda s_\lambda s_\lambda a_\lambda = \eta a_\lambda e_\lambda \ne 0$. Therefore the left ideal generated by $e_\tau$ can be rewritten in terms of $\tilde{e}_\tau$ as $e_\tau(a)=\sum_p \zeta_p \tilde{e}_\tau^p(a)$. Now, one has assumes that $\tau > \lambda$, so there are two numbers, namely $i$ and $j$, locate on the same line of the Young Tableaxu $\Theta_\tau$ and simultaneously on the same column of $\Theta_\lambda$. If not, following the argument used in the Appendix IV of the textbook, the two Young Tableaux must be the same, which leads to a contradiction. Therefore, if one multiplies the transportation $(ij)$ from the left of $e_\tau$ gives no effect: $(ij)e_\tau =e_\tau$, while an extra $-1$ is obtained in the case of $\tilde{e}_\lambda$: $(ij)\tilde{e}_\lambda^p= - \tilde{e}_\lambda^p$.

So one can apply $(ij)$ to both the contravariant indices and covariant indices of the contraction

$$T^{\tau(a)}T'_{\lambda(a)}=T^{(ij)\tau(a)}T'_{(ij)\lambda(a)},$$

and the above arguments give $$T^{(ij)\tau(a)}T'_{(ij)\lambda(a)}=-T^{(ij)e_\tau (a)}T'_{(ij)\sum_p \zeta_p \tilde{e}_\lambda^p (a)}=-T^{\tau(a)}T'_{\lambda(a)},$$

and therefore

$$T^{\tau(a)}T'_{\lambda(a)}=0.$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.